Comparative analysis of physicochemical properties, sensory characteristics, and volatile flavor compounds in five types of potato chips - Zhang, Qiaozhen; Sun, Yue; Sun, Yahui; Guo, Cui; Zhu, Jiayin; Niu, Xinkui; Gao, Mingshuang (Frontiers in Nutrition, 2025)
IntroductionPotato chips are the primary product of the potato leisure food market. And the level of consumer preference is strongly influenced by their flavor.MethodsIn this study, five potato chips were compared by combining their physicochemical properties, sensory characteristics, and volatile flavor compounds. The volatile flavor compounds in potato chips were evaluated using gas chromatography-ion mobility spectroscopy (GC-IMS).Results and discussionGC-IMS identified 57 volatile flavor compounds, including 17 aldehydes, 9 esters, 10 ketones, 3 pyrazines, 12 alcohols, 3 acids, 1 pyridine, and 2 ethers. Moreover, the aldehydes had the largest relative amount and kind. Seven identical key volatile flavor compounds with ROAV ≥ 1 were examined in five potato chips. In addition, the variety of key flavor compounds with ROAV ≥ 1 was more abundant in Leshi (LS) industrial fresh-cut fried potato chips. While the types of key volatile flavor compounds in Leshi (LS) industrial fresh-cut fried potato chips and other composite potato chips varied, the types of key volatile flavor compounds in composite fried and baked potato chips made with various formulations were consistent. In the sensory evaluation, Shuyuan (SY) industrial composite potato chips and Shiyanshi (SYS) homemade composite baked potato chips were preferred overall. The Leshi (LS) industrial fresh-cut fried potato chips and Kebike (KBK) industrial composite fried potato chips had greater relative levels of harmful factors. But none of the potato chips included trans-fatty acids. The correlation heatmap showed that the harmful factors in potato chips were mainly positively correlated with volatile flavor compounds such as aldehydes and ketones originating from the oxidative degradation of fat.ConclusionThe study provided a reference for choosing appropriate process conditions in potato chip processing so that the safety of the food can be enhanced while obtaining consumer-preferred food flavors.